MODERATING ROLE OF FINANCIAL INNOVATION ON THE RELATIONSHIP BETWEEN FINANCING DECISIONS AND FINANCIAL PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA - Rufai Mohammed Abdulrahman (Gusau Journal of Accounting and Finance)
The performance of deposit money banks in Nigeria over the last decade is faced with declining profitability, negative profit and inability to pay dividends over a period of time as a result of underperformance. This study investigates the moderating role of financial innovation on the relationship between financing decisions and financial performance of listed deposit money banks in Nigeria. Using a 15-year panel dataset (2009-2023) from 16 banks, and the methodology adopted for the study was descriptive research design employing random effects estimation to test the hypotheses using STATA 13 version software package. Secondary data was adopted, sourced from Nigeria Exchange Group facts book and banks annual financial reports for the period. The study finds that debt and equity financing significantly enhance performance, while risky and risk-free investments negatively affect ROA. Financial innovation significantly moderates these relationships. The study recommends cautious investment practices and greater adoption of financial technologies.